Common approach to formation of tests for knowledge control - Жирякова, Ірина Анатоліївна; Гладка, Людмила Іванівна (Eastern-European Journal of Enterprise Technologies, 2012)
Article is devoted to the unified development of the methodical approach to generate tests for qualitative monitoring of students knowledge from all forms of learning. In article the structure of the package tests for final control knowledge which agreed with the scale of ECTS first proposed